Enhancing students’ engagement and motivation in physical education: the role of fitness tracker apps - Rusmitaningsih, Fika Nuraini; Subarjah, Herman; Yustiana, Yusi Riksa; Saputra, Deddy Rahmat (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2024)
Background: The integration of technology in physical education (PE) has gained increasing attention for its potential to enhance student engagement and motivation. Fitness tracker applications, available on smartphones and wearables, offer innovative solutions for real-time feedback, activity monitoring, and motivational support. Research Objective: This study evaluates eleventh-grade students' perceptions of the effectiveness of fitness tracker apps in enhancing engagement and motivation in PE. Methods: The study was conducted with 60 students (30 males and 30 females) at Vocational High School 3 Tegal, Central Java, Indonesia. A mixed-methods approach was employed, combining quantitative data from structured questionnaires and fitness trackers with qualitative insights from semi-structured interviews and direct observations. Quantitative data were analysed using descriptive statistics and paired t-tests, while thematic analysis was applied to the qualitative data. Finding/Results: The quantitative results indicated significant improvements in student engagement, motivation, and awareness of physical fitness, with increased frequency of app usage and higher motivation to exercise (p < 0.05). Qualitative analysis revealed that students appreciated the real-time feedback and motivational features of the apps, which enhanced their overall enjoyment and commitment to physical activities. However, technical challenges such as data synchronisation issues and difficulties with initial setup were consistently reported by participants. Conclusion: Fitness tracker applications hold significant potential to enhance student engagement and motivation in PE. The relatively small sample size (60 students) may limit the generalisability of the findings. Future research should address this limitation by incorporating larger samples and exploring solutions to technical challenges.